Desain Karakter Pada Penciptaan Buku Golden Tiket Petualangan Kereta Api - Allifia, Zidni Enggar; Masnuna; Sutejo, Aris (UNIVERSITAS INDO GLOBAL MANDIRI, 2025)
The train adventure presented is about an adventure carried out by a child packaged in a fantasy story. This study aims to develop character designs in illustrated train travel books that utilize augmented reality (AR) technology for children aged 6-12 years. The research method involves analyzing literature related to character design, children's illustrations, and the application of augmented reality in interactive media. Data collection was carried out through literature studies, interviews with illustrators and children's book experts, and surveys of parents and children. The results of this study are the characters that will be used in illustrated books that combine short stories and the use of augmented reality. Character designs are created digitally with a cartoon drawing style, paying attention to the principles of illustration and the characteristics of the target readers. The implementation of augmented reality allows readers to interact directly with the book via a smartphone or tablet, displaying simple animations that bring the characters and tourist attractions in the story to life. The results of this study show the importance of character design that is appropriate to the target audience so that it can attract the attention of readers before seeing the entire contents of the illustrated book.